Phonetic notation in foreign language teaching and learning: potential advantages and learners’ views - Mompean, Jose A. (Research in Language, 2015)
This paper focuses on the use of phonetic notation in foreign language teaching and learning. The aim of the paper is twofold: first, we review some of the potential advantages that the use of phonetic notation seems to have in language teaching and learning; and secondly, the paper reports on learner views obtained with a questionnaire anonymously filled in by EFL (English as a foreign language) learners in tertiary education who followed an English course where an extensive use of phonetic symbols was made for pronunciation work in Finland, France and Spain. The results suggest that learners were relatively familiar with phonetic notation prior to their course although there were differences between countries. Phonetic notation was perceived positively by a majority of learners, particularly in terms of its perceived potential for raising awareness of the target language’s pronunciation features and its potential to visually represent sounds. Learners’ answers were also mostly positive regarding the potential of phonetic notation for autonomous learning, as well as the perceived ease and usefulness of phonetic notation.